2004
DOI: 10.1111/j.1464-5491.2004.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie B virus serology and Type 1 diabetes mellitus: a systematic review of published case‐control studies

Abstract: The results of these studies are inconsistent and do not provide convincing evidence for or against an association between Coxsackie B virus infection and Type 1 diabetes mellitus. Better designed studies using effective assays are needed to resolve this important issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 50 publications
(75 reference statements)
0
58
0
Order By: Relevance
“…The lack of this information could also explain the variable results from previous studies that have been based on assays detecting several different enterovirus types as a group (2,12). Despite the importance of this topic, large-scale systematic studies aimed at identifying diabetogenic enterovirus serotypes have not been performed.…”
mentioning
confidence: 56%
“…The lack of this information could also explain the variable results from previous studies that have been based on assays detecting several different enterovirus types as a group (2,12). Despite the importance of this topic, large-scale systematic studies aimed at identifying diabetogenic enterovirus serotypes have not been performed.…”
mentioning
confidence: 56%
“…Serological studies and studies detecting viruses in respiratory or stool samples detect exposure, but not invasion (Figure 2). In fact, this seems to be the case, since serological studies and the detection of EVs from stool samples have indicated only weak or no risk effect [21][22][23]. In contrast, studies based on virus detection from blood or pancreas have shown a risk effect [24,25].…”
Section: Role Of Non-inva-sive and Invasive Infectionmentioning
confidence: 90%
“…According to published meta-analyses, the association between EV and T1D is quite strong in studies which have been based on direct virus detection from blood or tissues (odds ratios ranging from 4 to 10) [24]. However, serological studies have shown more variable results [21], possibly because they measure the general exposure and not invasive infection. The discovery of IFIH1 as a risk gene for T1D has recently offered a feasible mechanistic explanation for this association [32,34].…”
Section: How To Prove Causality?mentioning
confidence: 99%
“…Rubella virus (Karvonen et al, 1993), mumps virus (Hyoty et al, 1988, cytomegalovirus (Ward et a., 1979), rotavirus (Honeyman et al, 2000) and enteroviruses (EV) (Lonnrot et al, 2000;Stene et al, 2010) have all been suggested as environmental factors contributing to type 1 diabetes. EV, especially those of the Coxsackievirus B (CVB) group (Hyöty et al, 1988;Varela-Calvino & Peakman , 2003;Green et al, 2004), are historically the prime suspects as important aetiological determinants and seroepidemiological, histopathological, animal studies, and in vitro experiments have provided the strongest overall evidence for these viruses. The EV genus of the Picornaviridae family is a large group of human pathogens traditionally divided into polioviruses, coxsackieviruses, echoviruses and the new EV, and each group contains a range of serotypes (King et al, 2000;Roivainen, 2006).…”
Section: Enteroviruses and Type 1 Diabetesmentioning
confidence: 99%